Correlation of Single Photon Emission Computed Tomography Results with Clinical and Intraoperative Findings in the Painful Total Ankle Replacement. Issue 4 (16th October 2019) - Gurbani, Ajay; Demetracopoulos, Constantine; O'Malley, Martin; Deland, Jonathan; Cody, Elizabeth; Sofka, Carolyn; Ellis, Scott
Category: Ankle Arthritis Introduction/Purpose: Determining the etiology of pain after total ankle replacement (TAR) often serves as a diagnostic dilemma for many surgeons, particularly in the setting of normal appearing radiographs. Single photon emission computed tomography (SPECT CT) has been identified as a potentially useful tool to evaluate pain after TAR. However, prior research has been limited by a lack of comparison to clinical findings as well as comparison to other imaging modalities. Our study aims to add to the current understanding of the role of SPECT CT as a diagnostic tool in TAR. It is our hypothesis that SPECT CT would be predictive of clinical and intraoperative findings in patients with pain after TAR. Methods: A retrospective review was undertaken of SPECT CT imaging performed at our institution for the evaluation of painful TAR from January 2014 to November 2018. There were 35 patients identified during this time period who underwent SPECT CT to evaluate pain after TAR. The average length of time from index surgery to SPECT CT was 17.2 months. Of this cohort, 18 patients also had an MRI during the same time frame and images were available for comparison. Findings on the imaging studies were compared to clinical findings as documented in the medical record, as well as intraoperative findings at the time of revision surgery when one was performed. SPECT CT results, as well as MRI results when available, were evaluated for their consistency with documented clinical and intraoperative findings. Results: Of the 35 patients, 91.4% (32/35) had SPECT CT results that were consistent with clinical findings. Amongst the diagnoses for which SPECT CT was useful in this cohort, loosening (12/32) and impingement (10/32) were most common. Other diagnoses included malalignment (4/32), cyst formation (2/32), subtalar arthritis (2/32), and infection (2/32). In our cohort, 25 patients underwent revision surgery, and SPECT CT imaging was consistent with ultimate intraoperative findings in 24 (96.0%) cases. Procedures performed were revision for aseptic loosening (11/25), gutter debridement (5/25), revision for malalignment (2/25), hindfoot reconstruction (2/25), implant removal for infection (2/25), cyst grafting, subtalar arthrodesis, and conversion to ankle arthrodesis. In the 18 patients who also underwent MRI, these results were consistent with clinical findings 38.9% (7/18) of the time. Conclusion: In this cohort, there was a high consistency between SPECT CT results and documented clinical diagnoses. Additionally, in those patients who ultimately underwent revision surgery, SPECT CT demonstrated high consistency with intraoperative findings. When compared to MRI, SPECT CT proved more useful in helping to establish a diagnosis for pain after TAR in our cohort. Our series serves to highlight the utility of SPECT CT as an additional tool in evaluating the painful TAR. Further investigation into the interpretation of SPECT CT after TAR, including changes in physiologic postoperative uptake that occur over time, is warranted.